Efek Substitusi Pakan Alternatif Maggot terhadap Produksi dan Pendapatan Usaha Ayam Petelur - Rafina Filaelevi Pramathitya; Arief, Hasni; Sondi Kuswaryan (SINTA Journal (Science, Technology, and Agricultural), 2025)
The laying farm is currently facing the problem of fluctuating feed prices.  Therefore, a solution is needed in the form of using alternative feed that can replace conventional feed to address this issue. This research was conducted at Bening saguling Foundation, Babak, Cihampelas, Cihampelas Subdistrict, West Bandung District, West Java.  The purpose of this study is to determine the effect of substituting alternative feed of maggot on production performance and Income Over Feed Cost (IOFC) in laying hens.  Data were collected from two intensive battery cage poultry with a total population of 4,621 birds.  The first cage was given alternative feed containing 21% maggots of the total feed, while the second cage was 100% conventional feed consisting of corn, concentrate, bran, and premix.  The maggots be used as alternative feed by produced  through self-cultivation utilizing organic waste.  This study employed a case study method with a quantitative approach.  The result showed  that the cage using 100% conventional feed achieved a hen day production of 85.40% and Income Over Feed Cost of IDR13,712 per bird per month.  Meanwhile, the cage fed with maggot alternative feed reached a hen day production of 86.44%   and Income  Over Feed Cost of IDR15,641  per  bird per month.